Socioeconomic and regional disparities in safe delivery in India (1990-2006) - Yadav, Jeetendra; Gupta, Shyama; Singh, Kh Jiten Kumar (International Journal Of Community Medicine And Public Health, 2016)
Background: Giving birth to a child is not only a strain for the body, but it also puts the woman’s health at risk. Globally, nearly 300,000 thousand women die each year as a result of pregnancy related complications. India, with a population of more than 1.21 billion, has the highest maternal mortality in the world (estimated to be 56000 in 2010). Addressing the maternity care needs of women may have considerable ramifications for achieving the Millennium Development Goal (MDG)-5. The proportion of births attended by skilled health personnel (safe delivery) is one of the main indicators used to monitor progress in reaching MDG 5. The main objective of this study was to the traces the changes in utilization patterns and determinants of safe delivery care services by women in India, during last one and half decade, 1990-2006. Methods: Data from three rounds of the Demographic and Health Survey (DHS), known as the National Family Health Survey (NFHS) in India were analyzed. Bivariate and multivariate-pooled logistic regression model were applied to assessing the trends and determinants of safe delivery care services utilization, over one and half decade, 1990-2006 and also fit models stratified by survey periods and with interactions among key socioeconomic predictors to show the extent of disparity in the utilization of safe delivery care services among women belonging to different socioeconomic strata. Results: The results from analysis indicate that the coverage of safe delivery has increased from 34 percent to 50 percent during the last one and half decade. Overall, it can be said that, there was an improvement in the level of safe deliveries over the period of time. This improvement was somewhere very marginal, but somewhere very pronounced too. The results shows those women’s education, husband’s education, religion, caste, mass media exposure, birth order and interval, wealth quintile and region of residence were found to be statistically significant determinants in the utilization of safe delivery care services. Women from the Southern region utilizing the highest safe delivery care services compared to other regions. Conclusions: The region specific inequalities, which were greater than the socioeconomic inequalities, may be reduced by expanding outreach health programs to bring services closer to the disadvantaged. Promoting the use of family planning, female education, targeting vulnerable groups such as poor, illiterate, high parity women, involving media and grass root level workers and collaboration between community leaders and health care system could be some important policy level interventions to address the unmet need of safe delivery care services among women. Maternity programmes should be designed keeping in mind the socioeconomic and geographically context, especially women who belongs to EAG states, India.